2022
DOI: 10.1097/sap.0000000000003106
|View full text |Cite
|
Sign up to set email alerts
|

Kimura Disease of the Thigh Treated With Surgical Excision and Dupilumab

Abstract: Kimura disease (KD) is a rare, chronic inflammatory disorder presenting with solitary or multiple masses. Treatment options include surgical excision, corticosteroids, and radiotherapy; however, optimal therapy remains to be established. Moreover, efficacy of a humanized monoclonal antibody, dupilumab (Dupixent), requires to be demonstrated. Here, we present a 36-year-old male patient with an enlarging mass in the left medial thigh and chronic eczema over the abdomen and lower legs. Kimura disease was diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Further reports were found for Kimura’s disease with 4 patients treated with dupilumab and 3/4 experiencing complete and one partial remission [ 232 , 233 , 234 , 235 ]. Four cases of steroid-refractory papuloerythroderma Ofuji treated with dupilumab all reported complete resolution of skin lesions and pruritus [ 236 , 237 , 238 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further reports were found for Kimura’s disease with 4 patients treated with dupilumab and 3/4 experiencing complete and one partial remission [ 232 , 233 , 234 , 235 ]. Four cases of steroid-refractory papuloerythroderma Ofuji treated with dupilumab all reported complete resolution of skin lesions and pruritus [ 236 , 237 , 238 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most frequently affected areas are the head and neck region, especially the parotid glands, salivary glands, and lymph nodes (9). Masses in other areas, such as the groin (10), breast (11), arm (12), thigh (13), and orbit (14), have also been reported. This study was consistent with previous studies that most lesions (14/16) were located in the head and neck region, but there were still two cases located in the back and elbow, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, six patients received combination therapy, and no recurrence has been reported until now, which is in line with the previous results. Several biological agents, such as benralizumab (41), an anti-IL-5 receptor antibody; mepolizumab, an anti-IL5 antibody (42); and dupilumab, a Th2 pathway-targeted agent (13), have been successfully used in the treatment of KD on a small scale, but the efficacy in pediatric patients still needs further validation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Szeto et al demonstrated a successful treatment of benralizumab with the long-standing efficacy of clinical improvement (19). Dupilumab also has been applied by Hsuan-Yu Huang et al and Yuichi Teraki et al with complete relief after 8-10 month of therapy (20,21).…”
Section: Discussionmentioning
confidence: 99%